A new trend in pathogenetic treatment of rheumatoid arthritis: tofacitinib, the first inhibitor of Janus kinase - Dmitry Evgenyevich Karateev (Современная ревматология, 2014)
The Problem of effective treatment of rheumatoid arthritis (RA) has not been solved yet. In patients with an inadequate response to the synthetic disease-modifying antirheumatic drugs (DMARDs), TNF inhibitors and other genetically engineered (GE) drugs may give an incomplete effect or be totally ineffective in 20–40% of cases. The search for new therapeutic options is very active in many directions, including modulation of intracellular signaling pathways. The most impressive clinical results in RA patients have been achieved for Janus kinase (JAK) inhibitor, tofacitinib, – Tofa (CP-690,550), a low molecular weight drug for oral administration. Unlike the conventional synthetic DMARD, Tofa belongs to targeted therapy drugs; its pharmacological effects largely resemble those of GE drugs (blockade of the biological effects of cytokines). In particular, some features of its mechanism of action (e.g., interleukin 6 inhibition) make it similar to tocilizumab. In all trials, Tofa proved to exhibit high clinical efficacy and satisfactory safety. Tofa was shown to be significantly more effective than methotrexate and placebo (in monotherapy, as well as in combination with DMARDs) in RA patients with an inadequate response to standard DMARDs and TNFa inhibitors (regarding response to treatment, individual parameters of disease activity, achievement of low disease activity and remission, functional impairment). Furthermore, Tofa can inhibit joint damage progression.